Late Wisconsinan Deglaciation and Champlain Sea Invasion in the St. Lawrence Valley, Québec - Parent, Michel; Occhietti, Serge (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1988)
ABSTRACTChamplain Sea history is directly linked to Late Wisconsinan deglacial episodes. Champlain Sea Phase I (Charlesbourg Phase) began in the Québec area at about 12.4 ka. It represented a western extension of the Goldthwait Sea between remnant Appalachian ice masses and the Laurentide Ice Sheet. Further south, at about the same time, in the Appalachian uplands and piedmont, high-level glacial lakes were impounded by the ice-front during glacial retreat toward NNW: lakes Vermont, Memphrémagog and Mégantic. Lowlands of the Upper St. Lawrence and Lake Champlain valleys were progressively deglaciated and inundated by Lake Iroquois and Lake Vermont. At about 12.1 ka, these two lakes coalesced and formed a single water-body, here referred to as Lake Candona. After the Ulverton-Tingwick Moraine was constructed, this lake extended northeastward onto the Appalachian piedmont where varved sediments containing Candona subtriangulata underlie marine clays. Current data and interpretations bring into question the former concept of the Highland Front Moraine System. The invasion of the main basin, or Champlain Sea Phase II, began around 12 ka. Replacement of Lake Candona by the sea resulted in a fall of about 60 m in water levels. Champlain Sea Phase III began at the end of the Saint-Narcisse episode, at about 10.8 ka. At this time marine waters were able to enter valleys of the Laurentian Highlands where brackish or fresh paramarine basins developed.